KDM6B histone demethylase is an epigenetic regulator of estrogen receptor β expression in human pleural mesothelioma. (September 2016) - Manente, Arcangela G; Pinton, Giulia; Zonca, Sara; Tavian, Daniela; Habib, Tanwir; Jithesh, Puthen V; Fennell, Dean; Nilsson, Stefan; Moro, Laura
Aim: To assess the correlation between KDM6B and estrogen receptor β (ERβ) expression in malignant pleural mesothelioma (MPM).Materials & methods: We evaluated gene expression by in silico analysis of microarray data, real-time PCR and western blot in MPM tumors and cell lines.Results & conclusion: We report a strong positive correlation between the expression of KDM6B and ERβ in MPM tumors and cell lines. We describe that, in hypoxia, the HIF2α–KDM6B axis induces an epithelioid morphology and ERβ expression in biphasic MPM cells with estrogen receptor-negative phenotype. Reduced histone H3K27 tri-methylation confirms KDM6B activity under hypoxic conditions. Importantly, cells treated during reoxygenation with the selective ERβ agonist, KB9520, maintain ERβ expression and the less aggressive phenotype acquired in hypoxia.